The Role of The Indonesian Ulama Council (MUI) in Combating The Covid-19 Pandemic in Indonesia - Sukri, Mhd Alfahjri (Institut Agama Islam Negeri Curup, 2023)
The aims of this study were to describe and analyse the role of MUI in an effort to tackle and reduce the impacts of coronavirus (Covid-19) in Indonesia. It used qualitative methods in the form of literature studies using various sources such as scientific work, journals, newspapers, and other related sources. The results showed that MUI as a Religious Non-Governmental Organization (NGO) which oversees Muslims played an important role in dealing with the coronavirus outbreak in Indonesia. This role could be seen from the actions of MUI issued some fatwas and approaches for Muslims and the Indonesian government. Fatwa number 18 of 2020 regarding the guidelines for managing the body, fatwa number 17 of 2020 concerning prayer guidelines for medical personnel, fatwa number 14 of 2020 regarding the conduct of religion in situation of the outbreak of covid-19, fatwa number 2 of 2021 concerning Covid-19 vaccine, etc. MUI also provides suggestions such as prohibiting the public to mudik, following the advice of scientists, and avoiding crowds. Fatwa and MUI advice helped the government in maintain social distance and physical distance as an effort to prevent the further spread of covid-19. The MUI has successfully fulfilled its role as a Religious NGO. Its actions demonstrate that Religious NGOs can make a positive contribution in assisting the government and fostering the development of democracy in Indonesia